2012
DOI: 10.1007/s00262-012-1268-7
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 gene polymorphism influences dendritic cell in vitro function and clinical outcomes in vaccinated melanoma patients

Abstract: Toll-like receptor 4 (TLR4) is expressed on dendritic cells (DCs), sensing environmental danger molecules that induce their activation and maturation. Recently, we reported a method for the production of therapeutic DCs against melanoma, called tumor antigen-presenting cells (TAPCells), using a heat-shocked allogeneic melanoma cell lysate (TRIMEL) as an activation factor and antigen provider. Since TRIMEL contains endogenous TLR4 ligands, we evaluated the role of TLR4 in TAPCells differentiation by antibody ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 44 publications
0
47
0
Order By: Relevance
“…Importantly, 60% of evaluated metastatic patients (62 of 102) developed a DTH reaction against TRIMEL, indicating the development of immunological memory against the tumor that correlates with prolonged survival of patients. The in vitro analysis of TRIMEL revealed that it contains DAMPs such as nuclear protein HMGB-1 induced by heat shock, which are capable of eliciting, through Toll-like receptors the maturation of DCs, improving TAA cross-presentation (Aguilera et al, 2011;Tittarelli et al, 2012). Tissue biopsies from DTH sites revealed the presence of CD45RO + CD8 + and CD4 + TL able to release pro-infl ammatory cytokines after in vitro stimulation.…”
Section: The Chilean Vaccine Against Melanoma: Clinical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, 60% of evaluated metastatic patients (62 of 102) developed a DTH reaction against TRIMEL, indicating the development of immunological memory against the tumor that correlates with prolonged survival of patients. The in vitro analysis of TRIMEL revealed that it contains DAMPs such as nuclear protein HMGB-1 induced by heat shock, which are capable of eliciting, through Toll-like receptors the maturation of DCs, improving TAA cross-presentation (Aguilera et al, 2011;Tittarelli et al, 2012). Tissue biopsies from DTH sites revealed the presence of CD45RO + CD8 + and CD4 + TL able to release pro-infl ammatory cytokines after in vitro stimulation.…”
Section: The Chilean Vaccine Against Melanoma: Clinical Resultsmentioning
confidence: 99%
“…This heat shock consists of exposing the cells to temperatures of 42 °C for a period of 1 hour and then 2 hours at physiological temperature (37 °C). Our data indicate that this conditioning of tumor cells from which the lysate is produced triggers danger signals that are essential to activate DCs and enhance antitumor signals to TL (Aguilera et al, 2011;Tittarelli et al, 2012;Reyes et al, 2013).…”
Section: Tapcells; the Chilean Research Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, TLRs appear to play a prominent role not only in the orchestration of innate immune responses against infectious pathogens, but also in anticancer immunity, be it spontaneous or elicited by (chemo)therapeutic interventions 23 , 27 , 57 , 58 . In accord with this notion, functionally relevant polymorphisms in the genes encoding several TLRs (i.e., TLR1, TLR2, TLR3, TLR4, TLR6, TLR9 and TLR10) have been shown to influence the natural development of a wide array of neoplasms, including tumors that are not associated with a microbial etiology, 59 - 77 as well as to affect the response of cancer patients to chemotherapy and immunotherapy, at least in some settings 54 , 78 - 80 . Moreover, the expression of several TLRs including TLR2, TLR4, TLR7 and TLR9 by malignant cells appear to evolve not only along with oncogenesis and tumor progression, but also in response to microenvironmental cues, 81 - 90 suggesting that, at least in some types of cancer, TLRs may influence disease progression in a direct fashion rather than as a consequence of immunological effects.…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, SNPs that reduce the activity of various TLRs have been shown to negatively impact the response of cancer patients to therapy in multiple scenarios 83 , 86 - 88 . At least in part, this reflects the key role that some TLRs play in the perception of cell death as immunogenic 79 , 80 .…”
Section: Introductionmentioning
confidence: 99%